2019
DOI: 10.3847/1538-4357/ab5521
|View full text |Cite
|
Sign up to set email alerts
|

The Canada–France Imaging Survey: Reconstructing the Milky Way Star Formation History from Its White Dwarf Population

Abstract: As the remnants of stars with initial masses 8 M , white dwarfs contain valuable information on the formation histories of stellar populations. In this paper, we use deep, high-quality, u-band photometry from the Canada France Imaging Survey (CFIS), griz photometry from Pan-STARRS 1 (PS1), as well as proper motions from Gaia DR2, to select 25,156 white dwarf candidates over ∼4500 deg 2 using a reduced proper motion diagram. We develop a new white dwarf population synthesis code that returns mock observations o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 103 publications
(143 reference statements)
8
72
1
Order By: Relevance
“…Finally, we remark that the ages of counter-rotating stars in the local vicinity make a reliable estimate for the time of the GES merger event, which has been found in Belokurov et al (2020) to be about 9.5 Gyr ago. Given the clear connection between the GES merger and a starburst of short duration, the identification of a clear peak in the SFH at early times may provide a good estimate of the merger time as well (see the recent works of Nogueras-Lara et al 2019;Fantin et al 2019, that find evidence for an early burst of star formation in the disc). As stellar age measurements improve in the future (e.g.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Finally, we remark that the ages of counter-rotating stars in the local vicinity make a reliable estimate for the time of the GES merger event, which has been found in Belokurov et al (2020) to be about 9.5 Gyr ago. Given the clear connection between the GES merger and a starburst of short duration, the identification of a clear peak in the SFH at early times may provide a good estimate of the merger time as well (see the recent works of Nogueras-Lara et al 2019;Fantin et al 2019, that find evidence for an early burst of star formation in the disc). As stellar age measurements improve in the future (e.g.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…(1) the crystallization bump is predicted to start too early and (2) the amplitude of the pile-up is significantly underestimated (see also Kilic et al 2020). These problems are a source of concern for the use of white dwarfs as cosmochronometers (Winget et al 1987;Oswalt et al 1996;Fontaine et al 2001;Kalirai 2012;Hansen et al 2013;Tremblay et al 2014;Kilic et al 2017;Isern 2019;Fantin et al 2019). Core crystallization is a significant event in the evolution of a white dwarf and an accurate description of this phenomenon is needed to generate reliable theoretical cooling sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Gilmore & Reid 1983), which suggests a thick-disc membership for WASP-98. If so, its age is likely to be old; for example, Fantin et al (2019) found all thick-disc stars to have formed at 9.8 ± 1.5 Gyr. This supports an age of roughly 10 Gyr for the WASP-98 system, but is unfortunately not a conclusive evidence.…”
Section: K I N E M At I C S O F T H E Wa S P -9 8 S Y S T E Mmentioning
confidence: 99%